A Reflection on the Theory of Adequate Cause with Emphasis on Iranian and Common Law - Siāmak Rahpeik; Nader Vellaei (آموزه‌‌های فقه مدني, 2020)
The criterion for determining the responsible cause is different in different perspectives. The actus (material) view identifies the responsible cause solely on the basis of criteria such as the time of creation of the cause; In contrast, conventional causal perspectives provide normative criteria for identifying the responsible cause. The cause, in proportion to the criterion of the predictability of the damage, explains the responsible cause in such a way that there is an appropriateness between the cause of the damage and the type of damage. Shortcomings The ability to predict damage is a criterion which is also used in the position of guilt detection and is also used to limit the level of responsibility in terms of some fair (equity and impartiality) considerations; Thus, it is necessary to explain the functions of this criterion in different positions. The approach of the Islamic Penal Code, enactment of 2013 (1392 in the Solar Hijri calendar), as the latest indicator of the will of the legislator, includes the obvious features of the appropriate cause. Criticisms of this approach are like the criticisms that have been made in Common Law, the realists have objected of appropriateness cause. It cannot be the cause in the legal world as an abstractive subject of merely mechanically, therefore the set of factors which cause the identifying of responsible cause has material and immaterial aspects. According to this study, the criterion of the ability to predict the damage is considered as an immaterial aspects of legal cause.